2003
DOI: 10.1016/s0008-6363(03)00358-4
|View full text |Cite
|
Sign up to set email alerts
|

Second window of ischemic preconditioning regulates mitochondrial permeability transition pore by enhancing Bcl-2 expression

Abstract: The cytoprotective effects of SWOP are dependent on PTP activation state and may involve upregulation of Bcl-2 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 28 publications
3
43
1
Order By: Relevance
“…The magnitude of immediate protection afforded by Gd in the current study is less than the protection reported with ischemic preconditioning (31% vs. 86% reduction in infarct size) (11), but the fact that Gd can be given one minute before reperfusion and still provide significant infarct reduction makes it perhaps more clinically important than ischemic preconditioning. In addition to these temporal relationships, we observed that a single dose of Gd confers delayed cardioprotection for up to 72 hours to an extent that is comparable to delayed cardioprotection observed with ischemic preconditioning (66% vs. 67% reduction in infarct size) (12). This effect may also have important clinical applications in revascularization procedures, where recurrent ischemia may occur early after the procedure from graft occlusion or PCI failure.…”
Section: Discussionsupporting
confidence: 58%
“…The magnitude of immediate protection afforded by Gd in the current study is less than the protection reported with ischemic preconditioning (31% vs. 86% reduction in infarct size) (11), but the fact that Gd can be given one minute before reperfusion and still provide significant infarct reduction makes it perhaps more clinically important than ischemic preconditioning. In addition to these temporal relationships, we observed that a single dose of Gd confers delayed cardioprotection for up to 72 hours to an extent that is comparable to delayed cardioprotection observed with ischemic preconditioning (66% vs. 67% reduction in infarct size) (12). This effect may also have important clinical applications in revascularization procedures, where recurrent ischemia may occur early after the procedure from graft occlusion or PCI failure.…”
Section: Discussionsupporting
confidence: 58%
“…Accordingly, the goals of the present study were to determine whether pretreatment with nicorandil, in the absence of ischemia, can reproduce the protective effect of the late phase of ischemic PC against myocardial infarction and to determine whether nicorandil-induced delayed cardioprotection is associated with expression of COX-2 and Bcl-2, which has previously been shown to increase 24 h after ischemic PC (51,59). All studies were performed in our well-established conscious rabbit model (51,59).…”
mentioning
confidence: 99%
“…The other possible reason could be that the mild stress in the form of food restriction and exercise, before cardiac ischemia and failure, conditions the myocardium against the formation of free radicals at a later date. This is similar to the protective effects of ischemic preconditioning, where mild ischemia before the prolonged ischemia can protect the myocardium from severe ischemic damage (21,22). Calorie restriction (CR) or food restriction (FR) must be considered separately from food starvation and defined as a reduction in calorie or food intake below the usual ad libitum intake without malnutrition.…”
Section: Discussionmentioning
confidence: 99%